(-4t+8)(4t+1)=0

Simple and best practice solution for (-4t+8)(4t+1)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (-4t+8)(4t+1)=0 equation:


Simplifying
(-4t + 8)(4t + 1) = 0

Reorder the terms:
(8 + -4t)(4t + 1) = 0

Reorder the terms:
(8 + -4t)(1 + 4t) = 0

Multiply (8 + -4t) * (1 + 4t)
(8(1 + 4t) + -4t * (1 + 4t)) = 0
((1 * 8 + 4t * 8) + -4t * (1 + 4t)) = 0
((8 + 32t) + -4t * (1 + 4t)) = 0
(8 + 32t + (1 * -4t + 4t * -4t)) = 0
(8 + 32t + (-4t + -16t2)) = 0

Combine like terms: 32t + -4t = 28t
(8 + 28t + -16t2) = 0

Solving
8 + 28t + -16t2 = 0

Solving for variable 't'.

Factor out the Greatest Common Factor (GCF), '4'.
4(2 + 7t + -4t2) = 0

Factor a trinomial.
4((2 + -1t)(1 + 4t)) = 0

Ignore the factor 4.

Subproblem 1

Set the factor '(2 + -1t)' equal to zero and attempt to solve: Simplifying 2 + -1t = 0 Solving 2 + -1t = 0 Move all terms containing t to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + -1t = 0 + -2 Combine like terms: 2 + -2 = 0 0 + -1t = 0 + -2 -1t = 0 + -2 Combine like terms: 0 + -2 = -2 -1t = -2 Divide each side by '-1'. t = 2 Simplifying t = 2

Subproblem 2

Set the factor '(1 + 4t)' equal to zero and attempt to solve: Simplifying 1 + 4t = 0 Solving 1 + 4t = 0 Move all terms containing t to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + 4t = 0 + -1 Combine like terms: 1 + -1 = 0 0 + 4t = 0 + -1 4t = 0 + -1 Combine like terms: 0 + -1 = -1 4t = -1 Divide each side by '4'. t = -0.25 Simplifying t = -0.25

Solution

t = {2, -0.25}

See similar equations:

| -5X+6/5=9X+7/2 | | 3x-5y=19 | | 180-x=2x+12 | | 3(2x+3)=-2x+2 | | 7(x-12)-11=22x-275 | | 5(2x-5)-3(x+1)-18x= | | (n-4)(n+4)=n-4 | | 2x-5=55+7x | | -(3)/(y-5)=(-(8)/5y-25)+1 | | -6(x+4)+158=13+25 | | t(3t+27)=66 | | -4/6x=12/24 | | 4x+56=5432 | | 5+7x=-x+53 | | -(2x^2y+4z)+4z-7x^2y= | | 8-2w=2 | | -2/6x=6/12 | | 84=12(12y+3) | | 2x+3*x-1= | | 7x-43=52 | | 3X+3/5=-2X-7/4 | | 4x^2-20x+10=0 | | -14-(-12)=x/2 | | 7-3(5t-10)=-67 | | x+3=12-1x | | 49=3x+9 | | -5x-10=2x+11 | | 52=3x+7 | | 17x+30=4(3x+6)+5x+6 | | 7y+3(y-9)=6(y+1)-2 | | 9(y-6)/2=-2y | | -29+7+(-18)+(-12)= |

Equations solver categories